2018
DOI: 10.1097/prs.0000000000004636
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use following Outpatient Breast Surgery: Are Physicians Part of the Problem?

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…Patients undergoing breast reduction stopped all narcotics by postoperative Day 30, whereas 7.1% of patients undergoing secondary breast reconstruction continued to use narcotics beyond postoperative Day 30. This supports the data that suggest breast cancer patients are at increased risk of chronic opioid use, perhaps due to patient risk factors such as confounding anxiety and/or depression often associated with the diagnosis of breast cancer [1,10] . The authors warned physicians to be cognizant of patient factors, such as a new cancer diagnosis, that put patients at higher risk of opioid dependence [10] .…”
Section: Peri Operative Pain Managementsupporting
confidence: 85%
See 3 more Smart Citations
“…Patients undergoing breast reduction stopped all narcotics by postoperative Day 30, whereas 7.1% of patients undergoing secondary breast reconstruction continued to use narcotics beyond postoperative Day 30. This supports the data that suggest breast cancer patients are at increased risk of chronic opioid use, perhaps due to patient risk factors such as confounding anxiety and/or depression often associated with the diagnosis of breast cancer [1,10] . The authors warned physicians to be cognizant of patient factors, such as a new cancer diagnosis, that put patients at higher risk of opioid dependence [10] .…”
Section: Peri Operative Pain Managementsupporting
confidence: 85%
“…Persistent opioid use and overprescribing of opioids is well studied within the surgical oncology patient population [10] . In a study by Lee et al [11] , the authors aimed to understand the risk of developing new persistent opioid use after curative-intent cancer surgery.…”
Section: Opioid Usementioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were seen in a study of opioid use following secondary reconstruction published by Hart et al, in which the authors reported that while prescribing 30 opioid pills provided patients with enough medication, there were many pills left unused. They also found that patients stopped using opioids by postoperative day 5, with an average of 18.6 excess tablets 8 . As would be expected, Park et al 7 report that opioid consumption is correlated with the extent/invasiveness of the surgical procedure.…”
mentioning
confidence: 98%